Psychological features of the influence of virtual communication (Actual Problems of Psychology in Educational Institutions, 2021)
The article investigates the phenomenon of virtualcommunication, defines its main characteristics and difference from realcommunication. The works of scientists, their conclusions on the impact ofvirtual communication are analyzed. The attitude of modern youth tovirtual communication is clarified. There was determined the influenceof virtual communication on the development of communication skills ofadolescents and teenagers. The results of research on this problem arepresented. Conclusions are made on the basis of the analyzed literatureand the conducted research, which testify to the possibility of positiveand negative influence of virtual communication on the development ofpersonal communication processes.
Keywords: virtual communication, real communication, development, degradation, psychological problems, communication skills